(untitled) (Research, Society and Development, 2025)
Maxillomandibular advancement (MMA) has become the main surgical alternative for adults with moderate to severe obstructive sleep apnea syndrome (OSAS) who do not achieve adequate control with conservative therapies. The aim of this study is to critically review evidence published between 2016 and 2025 regarding the efficacy, durability, quality of life, and safety of MMA. Studies involving adults undergoing surgery, with samples of ≥10 patients and objective outcomes related to respiratory efficacy, long-term stability, quality of life, or safety, were included. The analysis showed mean reductions of approximately 70% in the apnea–hypopnea index, with an overall surgical success rate above 80% and clinical cure (AHI < 5 events/h) in about one-third of patients. Respiratory benefits remained stable for up to ten years, supported by durable skeletal anchorage. Specific quality-of-life instruments indicated significant and sustained improvements in restorative sleep, vitality, and mental health. The safety profile revealed major complications in less than 2% of cases, with transient labiomental paresthesia being the most common adverse effect, usually reversible within a few months. It is concluded that MMA represents a long-term surgical solution that combines strong respiratory impact, structural stability, and overall improvement in well-being, provided it is applied with multidisciplinary planning and structured postoperative follow-up.